Surface chemical reaction between polycarbonate and kilo-electron-volt energy Ar+ ion in oxygen environment - Choi, WK; Koh, SK; Jung, HJ (A V S AMER INST PHYSICS, 1996)
In order to improve wettability of polycarbonate to triple distilled water, an Ar+ ion and an oxygen ion were irradiated on a polycarbonate (PC) surface under various oxygen flow rates. Doses of ions were changed from 5x10(14) to 5x10(16) ion/cm(2) in a range from 500 eV to 1.5 keV energy by a broad ion beam source. Wetting angle of PC was not reduced much with only Ar+ irradiation, but the wetting angle was significantly decreased by Ar+ ion irradiation with flowing oxygen gas and had a minimum of 12 degrees by 1 keV Ar+ ion irradiation at oxygen flow rate of 4 seem. Change in wettability by O-2(+) ion irradiation shows the similar feature as compared with those of Ar+ ion irradiation. In atomic force microscopy study, root mean square of surface roughness was changed from 14 to 22-27 Angstrom by Ar+ ion irradiation, to 26-30 Angstrom by Ar+ ion irradiation with the oxygen flow, but did not depend on amounts of ion fluence which indicates that the wetting angle change was not influenced by surface morphology. Improved wettability of modified polymer surface is explained in terms of a two-step process. Formation of hydrophilic groups on the polymer was identified by Fourier transform infrared and by the increase of carbonyl oxygen peak in O 1s x-ray photoemission spectroscopy spectra of PC in the sample modified by Ar+ ion irradiation with the oxygen flow. (C) 1996 American Vacuum Society.
Keywords: THIN-FILM ADHESION; BEAM-ENHANCED ADHESION; IRRADIATION; POLYIMIDE; POLY(ETHYLENE-TEREPHTHALATE); WETTABILITY; DEPOSITION; SIO2